Supply Chain Logistics in Multi-Level Just-in-Time Production Sequencing Problems - Thapa, Gyan Bahadur; Silvestrov, Sergei (Journal of the Institute of Engineering, 2016)
The multi-level just-in-time sequencing problem is one of the challenging research areas in supply chain management. In this paper, we present brief review and some recent research developments of just-in-time production systems together with supply chain logistics. Observing production flows and supply chain synchronization in production process, we present the mathematical models of just-in-time (JIT) sequencing problem in multi-level and single-level as nonlinear integer programming in terms of discrepancy functions under the specified constraints. Discrete apportionment approach is briefly reported as an efficient frontier for single-level. Journal of the Institute of Engineering, 2015, 11(1): 91-100